2019
DOI: 10.1002/pd.5503
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of fetuses with ventriculomegaly: An observational retrospective study

Abstract: Objective To investigate the prognosis of fetuses with ventriculomegaly (VM). Methods Clinical data were collected from 234 cases of fetal VM diagnosed by ultrasound between March 2010 and July 2016. VM progression was monitored, and karyotyping and infection screening performed. Magnetic resonance imaging (MRI) was performed where increasing ventricular diameter was noted. Neonatal behavioral neurological assessment (NBNA) was carried out after birth, and Bayley Scales of Infant Development assessment at 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…However, there are many studies on the postnatal follow-up of isolated VM. [31][32][33] In conclusion, this study found that antenatal MRI is beneficial in cases with isolated VM and is especially helpful in cases with moderate VM, anterior placenta, mothers with higher BMI, and in the diagnosis of high-grade intracranial hemorrhage accompanying mild or moderate VM. We recommend performing an antenatal MRI for all fetuses with isolated VM.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, there are many studies on the postnatal follow-up of isolated VM. [31][32][33] In conclusion, this study found that antenatal MRI is beneficial in cases with isolated VM and is especially helpful in cases with moderate VM, anterior placenta, mothers with higher BMI, and in the diagnosis of high-grade intracranial hemorrhage accompanying mild or moderate VM. We recommend performing an antenatal MRI for all fetuses with isolated VM.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, we were unable to determine the postnatal outcomes of isolated VM. However, there are many studies on the postnatal follow‐up of isolated VM 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…Progression of ventriculomegaly was defined as ventricular enlargement greater than 2 mm compared with the initial measurement. Stable ventriculomegaly was defined as an enlargement of less than 2 mm, and regressive ventriculomegaly was defined as a decrease of 2 mm or more or as a ventricular diameter of less than 10 mm [8,13].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Progression of ventriculomegaly was de ned as ventricular enlargement of greater than 2 mm compared with the initial measurement. Stable ventriculomegaly was de ned as an enlargement of less than 2 mm, and regressive ventriculomegaly was de ned as a decrease of 2 mm or more or as a ventricular diameter of less than 10 mm 9,14 .…”
Section: Ultrasoundmentioning
confidence: 99%